The Critical Role of Entrepreneurship and Innovation in Enhancing Community Economic Development and Growth - Desi Rahmawati (Lafadz Jaya Publisher, 2025)
Entrepreneurship and innovation are widely recognized as key drivers for economic development and societal progress. This paper explores the critical importance of entrepreneurship and innovation within communities as mechanisms to improve economic performance and foster sustainable growth. The study reviews existing literature to understand how entrepreneurial activities and innovative processes contribute to employment generation, income improvement, and poverty alleviation. A descriptive qualitative method was employed to analyze the impact of entrepreneurial initiatives and innovative strategies at the community level. The findings suggest that entrepreneurship encourages resource mobilization, promotes creativity, and supports the diversification of economic activities, while innovation enhances competitiveness and adaptability in dynamic markets. Furthermore, entrepreneurial ecosystems foster knowledge sharing, access to finance, and policy support, all of which are essential for nurturing innovation. The discussion highlights challenges faced by communities such as limited access to capital, inadequate infrastructure, and educational barriers, proposing integrated approaches to overcome these constraints. This study underscores the need for government and private sector collaboration to build an enabling environment that empowers local entrepreneurs and innovators. In conclusion, entrepreneurship and innovation are indispensable for strengthening the economic foundation of communities and achieving inclusive development. This research contributes to policy formulation aimed at economic revitalization through entrepreneurial and innovative interventions.